SDIT SALSABILA KLASEMAN YOGYAKARTA DENGAN PENEKANAN TEORI WOVEN ARCHITECTURE : WOVEN GARDEN Landasan Konseptual Perencanaan Dan Perancangan - , GAYATRI SOLFARINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Integrated Islam Elementary School or SDIT become the choice of many people because of its system which is comprehensive and integrative in learning, which combines general knowledge, religion, and the practice of learning into a single unit which is then imparted to the students. SDIT Salsabila Klaseman which located in Sinduharjo, Ngaglik, Sleman, Yogyakarta being the choice case for the analysis and concept made. SDIT which was established on 1 July 2004 was founded by activists division of LPI (Institute of Islamic Education) Foundation for Preaching and Education Center SPA (Lovers Gathering Children) led by RUA Zaenal Fanani, M.Prac along with education and community leaders about. Starting from the second-floor study room Rhoudatun Na'im Masjid Klaseman RT 06/38 Ngabean, Sinduharjo, Ngaglik, Sleman, Yogyakarta due to not yet have its own building, which then over time relocates to the house of the family estates Partiman Achmad drh (the late) , its loceted just 400m to the east of the mosque Rhoudatun Na'im. Schools building that placed in a former residential house and the increased of space requirements due to an increase in the number of students each year make this SDIT still require development or change in some parts of the entire building. With an emphasis on theory Woven Architecture and shape the concept of \"Woven Garden\" author tries renovate the shape of space, buildings, and access roads in and out of site locations which is also strong, durable, safe and accordance with the primary function of the building as a place of learning for children students of SDIT Salsabila Klaseman Yogyakarta.